The peculiarities of teaching pathophysiology to eglishspeaking students - Melnikova, O. V.; Мельнікова, Ольга Валеріївна (Особливості викладання патофізіології англомовним студентам, 2014)
The peculiarities in reality of the education process teaching pathophysiology subject to English-speaking students were summarized, an attempt to work out the recommendations for the academic process organization was made. В статті узагальнені особливості викладання патофізіології англомовним студентам, зроблена спроба розробки рекомендацій з організації навчального процесу.
Keywords: teaching; Pathophysiology; English-speaking students; викладання; патофізіологія; англомовні студенти